Free field representation and form factors of the chiral Gross-Neveu model - BRITTON, STEPHEN K; FROLOV, SERGEY (My University, 2013)
The free field representation of the Zamolodchikov-Faddeev algebra for the chiral Gross-Neveu model is analysed in detail, and used to construct an integral representation for form factors of the model
PUBLISHED
Keywords: Pure & Applied Mathematics